Influence of Amides and Salts on the Oxidation of Methyl Acetone and Ethyl Acetate by Potassium Dichromate - Guard, H.Z.; Kothwala, D.M.; Joshi, D.R.; Nagar, T.N. (Asian Journal of Chemistry, 2010)
In this paper, we are reporting the kinetics of oxidation of methyl acetate and ethyl acetate by potassium dichromate in acid-water and solvents-water mixtures using amides, salts and surfactants.